New floristic records, amendments and other phytogeographical notes from the Balearic Islands - Sáez, Llorenç; Serapio, Jordi; Medina, Leopoldo; Lloret, Ferran; Guasp, Elisabet; Vicens, Magdalena; Costa, Santi; Valls, Pere; Moreno Moral, Gonzalo; Domínguez, Luis Alberto; Bibiloni, Gabriel; Rita, Joan; et al. (UMA Editorial, 2022)
This paper deals with 61 taxa, 8 of which are new to the Balearic Islands flora: Bromus macrantherus Trab., Buglossoides incrassata subsp. splitgerberi (Guss.) E. Zippel & Selvi, Erodium neuradifolium Godr., Hedera helix subsp. rhizomatifera McAllister, Misopates calycinum (Vent.) Rothm., Narcissus serotinus L., Orobanche balsensis (J.A. Guim.) Carlón, M. Laínz, Moreno Mor. & Ó. Sánchez and Valerianella locusta (L.) Laterr. subsp. locusta. On the other hand, 8 species [Aira multiculmis Dumort., Aira uniaristata Lag. & Rodr., Oenanthe croccata L., O. pimpinelloides L., Opopanax chironium W.D.J. Koch, Puccinellia distans (Jacq.) Parl., Silene niceensis All. and Tyrimnus leucographus (L.) Cass.] are removed from the list of the Balearic Islands. Moreover, individual island reports are given for several species, 26 of them representing novelty at island level.

Este artículo incluye datos de 61 taxones, 8 de los cuales son nuevos para la flora de las Islas Baleares: Bromus macrantherus Trab., Buglossoides incrassata subsp. splitgerberi (Guss.) E. Zippel & Selvi, Erodium neuradifolium Godr., Hedera helix subsp. rhizomatifera McAllister, Misopates calycinum (Vent.) Rothm., Narcissus serotinus L., Orobanche balsensis (J.A. Guim.) Carlón, M. Laínz, Moreno Mor. & Ó. Sánchez y Valerianella locusta (L.) Laterr. subsp. locusta. Por otra parte, 8 especies [Aira multiculmis Dumort., Aira uniaristata Lag. & Rodr., Oenanthe croccata L., O. pimpinelloides L., Opopanax chironium W.D.J. Koch, Puccinellia distans (Jacq.) Parl., Silene niceensis All. and Tyrimnus leucographus (L.) Cass.] se excluyen del catálogo florístico de Baleares. Además, se proporcionan datos corológicos novedosos para varias especies, 26 de las cuales representan novedad a nivel insular.
Nuevos datos florísticos, correcciones y otras notas fitogeográficas de las Islas Baleares.
Keywords: Flora - Mediterráneo (Región); Plantas - Clasificación; Fitogeografía; Plantas autóctonas; Región Mediteránea; Taxonomía; Corología